Caribbean labour market challenges and policies - Downes, Andrew S. (CEPAL SantiagoCL, 2006)
Examines the challenges facing the labour market in the Caribbean. Suggests several policy measures for dealing with these challenges viz. educational and training reform; gainsharing schemes; export promotion; greater social dialogue; revised labour legislation; establishment of mutually advantageous relations with citizens living outside of the region; and, development of a labour market information system.